PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lisa Aprilliana; Dwi Susilowati; Nadi Hernadi Moorcy (Fakultas Ekonomi Universitas Balikpapan, 2023)
The purpose of this study is to determine the influence of Current Ratio, Debt To Equity Ratio, Total Asset Turnover and Return On Assets on Stock Prices in Food and Beverage Companies Listed on the Indonesia Stock Exchange. The data analysis technique used is multiple linear analysis by conducting anova test, classical assumption test, and partial hypothesis testing (t-test). The results showed that the Current Ratio variable had a negative and insignificant effect on stock prices, while the Debt To Equity Ratio variable had a positive and insignificant effect, Total Asset Turnover and Return On Assets had a positive and significant effect on stock prices